Assessing the impact of 24-hour activity behaviors on cardiorespiratory fitness in the older adult: a component analysis approach - Donglei Lu; Wenyu Zhang; Sijie Tan (Frontiers Media S.A., 2024)
BackgroundCardiorespiratory fitness (CRF) serves as a critical measure of the cardiovascular system's efficiency in delivering oxygenated blood to tissues and organs. Understanding the relationship between various activity behaviors and CRF is essential for devising effective health interventions for the older adult population.ObjectiveThis study aimed to investigate the association between 24-h activity behaviors and CRF in older adult individuals, utilizing compositional data analysis.MethodsWe utilized baseline data from the "Fifth National Physical Fitness Monitoring Cohort Study in Tianjin, China," which included 540 older adult participants. Physical activity and sedentary behavior were objectively measured using a three-dimensional accelerometer, and CRF was assessed via a gas metabolism analyzer. Compositional data analysis was employed to examine the relationships between 24-h activity behaviors-specifically, moderate-to-vigorous physical activity (MVPA), light physical activity (LPA), sedentary behavior (SB), and sleep (SLP)-and CRF.ResultsThe analysis demonstrated that MVPA was significantly positively associated with CRF (βMVPA = 5.36, p < 0.01), whereas SB was significantly negatively associated (βSB = −3.97, p < 0.01). No significant associations were observed for LPA and SLP with CRF. The isochronous substitution model revealed that reallocating 15 min of MVPA to SB, LPA, or SLP significantly decreased CRF by 0.31, 0.27, and 0.23 mL/kg/min, respectively. Conversely, substituting 15 min of SB, LPA, or SLP with MVPA resulted in increases in CRF by 0.29, 0.22, and 0.17 mL/kg/min, respectively. Additionally, replacing SB with LPA or SLP led to improvements in CRF, though these changes were not significant, underscoring the potential benefits of reducing sedentary time and enhancing physical activity levels.ConclusionThese findings underscore the critical role of increasing MVPA and reducing SB in improving CRF among the older adult. This study provides a robust scientific foundation for health promotion and intervention strategies targeting older adults. Comprehensive modifications to daily activity patterns are imperative for optimizing cardiovascular health in this population.